2018
DOI: 10.1101/471151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reward Modulates Local Field Potentials, Spiking Activity and Spike-Field Coherence in the Primary Motor Cortex

Abstract: Number of words (Abstract): Number of words (Significance Statement): Number of words (Introduction): Number of words (Discussion):Conflict of Interest: The authors declare no conflict of interests. ABSTRACTReward modulation of the primary motor cortex (M1) could be exploited in developing an autonomously updating brain-machine interface (BMI) based on a reinforcement learning architecture. In order to understand the multifaceted effects of reward on M1 activity, we investigated how neural spiking, oscillatory… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…This latter finding is similar to our previous observation that M1, S1 and dorsal premotor (pMd) neurons in primates increase their firing rates when the animal's reward expectation is not met 54,55 . A recent study showed that M1 LFP spectral power in the 8-14 Hz band increased in non-rewarding trials as compared to rewarded trials in a primate center-out reaching task 56 . This is consistent with the increase in spectral power observed in our study when encoder rats didn't receive a feedback reward in our study.…”
Section: Discussionmentioning
confidence: 98%
“…This latter finding is similar to our previous observation that M1, S1 and dorsal premotor (pMd) neurons in primates increase their firing rates when the animal's reward expectation is not met 54,55 . A recent study showed that M1 LFP spectral power in the 8-14 Hz band increased in non-rewarding trials as compared to rewarded trials in a primate center-out reaching task 56 . This is consistent with the increase in spectral power observed in our study when encoder rats didn't receive a feedback reward in our study.…”
Section: Discussionmentioning
confidence: 98%
“…We recently showed that this reward modulation of directional tuning holds during intracortical brain computer interface control (iBCI) when utilizing M1 (23), and that M1 grip force tuning functions are modulated by reward during manual control (23). In addition, we have recently discovered that reward modulation influences the relationship in M1 between the local field and individual neurons, where the spike field coherence is upregulated during nonrewarding trials as is the phase amplitude coupling between alpha phase and gamma amplitude (24).…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, M1, S1 and dorsal premotor (pMd) neurons in primates increase their firing rates when reward expectation is not met 54,55 . A recent study showed that M1 LFP spectral power in the 8-14 Hz band increased in non-rewarding trials as compared to rewarded trials in a primate center-out reaching task 56 . This is consistent with the increase in spectral power observed when encoder rats didn't receive a feedback reward in our study.…”
Section: Discussionmentioning
confidence: 98%